Application of The Principles of Extraterritorial Jurisdiction Towards Personal Data Breach Committed Cross-Country Borders - Ba'abud, Mohammad Fadel Roihan; Heriyanto, Dodik Setiawan Nur (Uti Possidetis: Journal of International Law, 2024)
Cybercrime is a reality that has emerged with the era of digitalization. One of the most commonly occurring cybercrimes is personal data theft. In light of Regulation No. 27 of 2022 regarding the Protection of Personal Data, which has extraterritorial application, it is essential to critically assess the jurisdiction applied to offenders involved in transnational personal data theft. The writer conducted normative research for this narrative, utilizing various scientific approaches such as statute, conceptual, and comparative analysis. This research uses Regulation No. 27 of 2022 as the analytical tool for domestic regulation towards the different conventions and regulatory frameworks within international law pertaining to the enforcement of personal data theft. The research leads to the conclusion that a domestic regulation with extraterritorial traits alone is not the ultimate solution for successfully applying extraterritorial jurisdiction for transnational offenders. In summary, an international framework that promotes and sustains intensive international cooperation is necessary to effectively enforce extraterritorial jurisdiction against offenders involved in transnationally committed personal data theft.